1999
DOI: 10.1523/jneurosci.19-13-05602.1999
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Neurons in V1 of Awake Monkeys Are Selective for Absolute, Not Relative, Disparity

Abstract: Most neurophysiological accounts of disparity selectivity in neurons of the primary visual cortex (V1) imply that they are selective for absolute retinal disparities. By contrast, a number of psychophysical observations indicate that relative disparities play a more important role in depth perception. During recordings from disparity selective neurons in area V1 of awake behaving monkeys, we used a disparity feedback loop () to add controlled amounts of absolute disparity to a display containing both absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(210 citation statements)
references
References 47 publications
12
197
1
Order By: Relevance
“…We minimized the matching problem by using a mixture of well spaced texture elements. In monkey, the cortical disparity sensitive cells in V1, generally believed to form part of the neural pathways for disparity vergence, are sensitive to absolute retinal disparity (Cumming and Parker 1999), as would be expected for cells mediating vergence. In cat striate cortex, von der Heydt et al (1978) reported that disparity selective cells have a range of preferred disparity with a mean preferred disparity of zero and a standard deviation of about 0.5°.…”
Section: Depth Selectivitymentioning
confidence: 86%
“…We minimized the matching problem by using a mixture of well spaced texture elements. In monkey, the cortical disparity sensitive cells in V1, generally believed to form part of the neural pathways for disparity vergence, are sensitive to absolute retinal disparity (Cumming and Parker 1999), as would be expected for cells mediating vergence. In cat striate cortex, von der Heydt et al (1978) reported that disparity selective cells have a range of preferred disparity with a mean preferred disparity of zero and a standard deviation of about 0.5°.…”
Section: Depth Selectivitymentioning
confidence: 86%
“…Both animals were implanted with scleral search coils in both eyes (Judge et al, 1980), head fixation posts, and a recording chamber over the operculum of V1 under general anesthesia. A detailed description of the methods is given by Cumming and Parker (1999). All procedures were in agreement with the Public Health Service policy on the humane care and use of laboratory animals, and all protocols were approved by the Institute Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Neurophysiological studies by Barlow et al (1967) and Pettigrew et al (1968) described disparity-selective neurons in the primary visual cortex (V1) of anesthetized cats and provided Wrst evidence for binocular disparity in V1 as a possible basis for stereopsis. Subsequent studies in alert, Wxating monkeys conWrmed the concept of stereopsis in the early visual areas (Poggio and Fischer 1977;Poggio et al 1988;Cumming and Parker 1999). The exact mechanisms underlying stereopsis, however, are still unknown and have been a matter of discussion for years (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the assumption that stereopsis is equivalent to depth perception (Barlow et al 1967). Although this hypothesis is no longer valid (Cumming and Parker 1999), it remains that neurons in V1 perform essential preprocessing underlying stereoscopic depth perception in higher areas.…”
Section: Introductionmentioning
confidence: 99%